Regional high iron deposition is linked with cognitive impairments in peritoneal dialysis: a quantitative susceptibility mapping study - Li, Dashan; Yin, Yongjie; Jiang, Shan; Yin, Jiuyu; Yu, Luyao; Feng, Nan; Sun, Zhaohua; Chen, Zilian; Xu, Hongting; Zhou, Yu; Fang, Jie; Qi, Xiangming; et al. (Frontiers in Aging Neuroscience, 2025)
ObjectivePeritoneal dialysis (PD) patients demonstrate distinct iron homeostasis imbalances. However, the relationship between brain iron and cognitive impairment in this population remains poorly elucidated.MethodsThis study enrolled 52 PD patients and 49 healthy controls (HCs). Quantitative susceptibility mapping (QSM) was employed to quantify cerebral iron deposition. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) and a comprehensive neuropsychological test battery. Dose–response relationships between iron metabolism parameters and cognitive performance were analyzed using generalized additive models (GAMs).ResultsPD patients exhibited significantly higher iron deposition in the left amygdala and right putamen compared to HCs. Serum ferritin (SF) demonstrated an approximately inverted U-shaped relationship with MoCA scores, with an inflection point at 258.4 μg/L (p < 0.001). Every 100 μg/L increase in SF beyond this threshold was associated with a 3.1-point decrease in MoCA score. Iron deposition in the left amygdala showed significant correlations with scores on the Digit Symbol Test (DST), Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), and Verbal Fluency Test (VFT), but exhibited no direct association with peripheral iron metabolism parameters.ConclusionIn peritoneal dialysis patients, abnormal cerebral iron deposition predominantly localizes to limbic-basal ganglia regions. Iron accumulation in the left amygdala may specifically mediate the development of multi-domain cognitive impairment. QSM represents a sensitive technique for early detection of pathological iron accumulation.